THE SEVEN-STAR DOCTOR: SYNCHRONIZING THE PMDC, WHO, AND PUMHSW’S ASPIRATIONS FOR EDUCATIONAL DISTINCTION IN HEALTH. : J Peop Univ Med Health Sci. 2025:15(2),1-4. http://doi.org/10.46536/jpumhs/2025/15.02.617 - PROF ANWAR ALI JAMALI , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
The Seven-Star Doctor is a concept put forth by the World Health Organization (WHO) which looks to reframe the role of medical practitioners in the 21st century1. It elaborates on the seven critical functions of a doctor which include: care provider, decision maker, a communicator, a leader of the community, a manager, an advocate for health,